Skin and other stories - Dahl, Roald, 1916-1990. (New York : Viking, 2000)
Introduces teenagers to the adult short stories of Roald Dahl.
Skin -- Lamb to the slaughter -- The sound machine -- An African story -- Galloping Foxley -- The wish -- The surgeon -- Dip in the pool -- The champion of the world -- Beware of the dog -- My lady love, my dove.
"First published in Great Britain in 2000 by Puffin Books"--T.p. verso.
Book Report.
Booklist.
Wilson's Junior High School.
Young Adult
Keywords: Short stories, English; Short stories; Short stories